IMPORTANCE OF RECEPTION FOR PREVENTING DISEASES CARDIOVASCULAR IN PRIMARY HEALTH CARE - Freitas, João Victor; Ana Beatriz Souza de Carvalho; Flávia Maria Costa Sena; Geórgia Alves Brito Isaías; Idrys Henrique Leite Guedes; Maria Eduarda Mesquita do Nascimento; Bruna Aderita Cortez de Sena (Health and Society, 2021)
Primary Health Care (PHC) is a great differential in the prevention of cardiovascular diseases, as its effectiveness contributes to reducing the worsening of health problems and, consequently, in the patient’s hospitalization. Based on this interrelationship, evidence from databases that correlated the reception performed in the PHC with the prevention of Cardiovascular Diseases (CVD) was incorporated. In the light of the chosen articles, not only the consequences of deficiencies in PHC were expressed, but also the satisfactory outcomes that occur when its dynamics are well structured and efficient, concomitantly built on principles involving disease prevention and health promotion, which they draw in expressive results such as lower rates of preventable deaths, as well as the decrease in the number of hospitalizations due to Heart Failure and Stroke.